2014
DOI: 10.1016/j.ejc.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The fractional chromatic number of triangle-free subcubic graphs

Abstract: Heckman and Thomas conjectured that the fractional chromatic number of any triangle-free subcubic graph is at most 14/5. Improving on estimates of Hatami and Zhu and of Lu and Peng, we prove that the fractional chromatic number of any triangle-free subcubic graph is at most 32/11 ≈ 2.909.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We remark that this lemma is most sensibly applied when X is a clique. 3 The unweighted version is described as folklore in [8] and was used earlier in [11], and probably elsewhere.…”
Section: Fractionally Colouring Weighted and Unweighted Graphsmentioning
confidence: 99%
“…We remark that this lemma is most sensibly applied when X is a clique. 3 The unweighted version is described as folklore in [8] and was used earlier in [11], and probably elsewhere.…”
Section: Fractionally Colouring Weighted and Unweighted Graphsmentioning
confidence: 99%
“…There are also two very recent improvements on the upper bound -but with totally different approaches. The first one is due to Ferguson, Kaiser and Král' [7], who showed that the fractional chromatic number is at most 32/11 ≈ 2.909. The other one is due to Liu [16], who improved the upper bound to 43/15 ≈ 2.867.…”
Section: History Of the Problem And Related Resultsmentioning
confidence: 99%
“…Lu and Peng [11] improved the bound to χ f (G) ≤ 3 − 3/43 ≈ 2.930. Ferguson, Kaiser and Král' [4] further improved that χ f (G) ≤ 32/11 ≈ 2.909. In this paper, we prove the following theorem.…”
Section: Introductionmentioning
confidence: 93%